Platelet-rich plasma in combination with bovine derived xenograft in the treatment of deep intrabony periodontal defects: A report of 20 consecutively treated patients - (:unkn) unknown (TAYLOR & FRANCIS INC, 2009)
There is currently great interest concerning the use of platelet-rich plasma (PRP) in combination with bone grafts for predictably obtaining periodontal regeneration. The aim of the present study was to investigate the effectiveness of PRP and bovine derived xenograft (BDX) combination in the treatment of deep intrabony defects with an emphasis on the evaluation of early wound healing. A total of 85 intrabony defects with an intrabony component of >= 3 mm were selected in 20 advanced chronic periodontitis patients. Defects were surgically treated with PRP/BDX. At baseline and 12 months after surgery, the following parameters were recorded: plaque and sulcus bleeding indices, probing depth (PD), relative attachment level, marginal recession (REC), probing bone and radiographic bone levels. Postoperative healing was evaluated by an early healing index at 1 and 2 weeks after surgery. At 12 months, all clinical and radiographic parameters were improved (p<0.0001). The mean changes at 12 months were: PD reduction of 4.78 +/- 1.20 mm, attachment gain of 4.24 +/- 1.03 mm, REC of 0.54 +/- 0.34 mm, clinical bone gain of 3.75 +/- 0.97 mm, and radiographic bone gain of 3.79 +/- 1.02 mm, respectively. Two weeks after surgery, primary closure was maintained in 95% of the defect sites. Treatment with a combination of PRP and BDX leads to a significantly favorable clinical and radiographic improvement in deep intrabony periodontal defects.
Keywords: Intrabony defects; periodontal regeneration; platelet-rich plasma; bovine derived xenograft; bone grafts; GUIDED TISSUE REGENERATION; CELLS-IN-VITRO; EXPANDED POLYTETRAFLUOROETHYLENE MEMBRANES; DRIED BONE ALLOGRAFT; GROWTH-FACTOR-BETA; CLINICAL-TRIAL; SPLIT-MOUTH; FACTOR-BB; ATTACHMENT; THERAPY